Mendialogkan Hermeneutika Doa dalam Kisah Ibrāhīm dan Mūsā - Mohammad Anwar Syarifuddin; Jauhar Azizy (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2014)
Taking hermeneutical approaches, the present research tries to provide a new form of Qur’ānic interpretation of supplications comprised within the history of Abraham and Moses. Two ways to be conducted in this research: First, to apply Hirsch’s hermeneutics theory in reconstructing meanings as found in classical tafsir. Second, to excavate significances of the supplication verses on the basis of their validly verbal meanings. This last attempt is to apply some reconciliatory theses of Palmer’s “hermeneutics manifesto” to enliven meanings.Keywords: Hermeneutic of the Qur’ān, theory of holy scripture interpretation, verses of supplication, history of the prophets.DOI: 10.15408/ref.v13i6.997